PENGARUH PENAMBAHAN UREA DAN AMONIUM KARBONAT PADA PEREKAT UREA FORMAIDEHIDA TERHADAP EMISI FORMALDEHIDA DAN SIFAT FISIS-MEKANIS PAPAN PARTIKEL - Paribotro Sutigno; Adl Santoso (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
The formaldehye emission of particleboard bonded with urea formaldehyde (UFJ cain affect human hseith. sepecially if It used in a room with limited ventilation. To reduce formaldehyde emission, the glue can be mixed with catching agent. In this paper, the effect of using urea and ammonium carbonate as catching agents on fermaldehyde emission,and on the physical and mechanical properties of UF bonded particleboard is described.the effect of catching agent type on formaldehyde emission is not signifivant while effect of percentage,of catching agent is highly significant on formaldehyde emission. The higher the percentage of catching agent, the lower formaldehye emission of particleboard. The formaldehyde emission reaches the requirement (max. 1 ug/ml) at the leve of 18% of amntonium carbonate or 14% of the mixture of ammonium carbonate and urea. Type and percentage of catching agent aflect water absoprtion, thickness swelling, internal bond strength,shear strength and modulus of rupture,but not the modulus of elasticity.